Hemodynamics and Subclinical Leaflet Thrombosis in Low-Risk Patients Undergoing Transcatheter Aortic Valve Replacement. (December 2019) - Khan, Jaffar M.; Rogers, Toby; Waksman, Ron; Torguson, Rebecca; Weissman, Gaby; Medvedofsky, Diego; Craig, Paige E.; Zhang, Cheng; Gordon, Paul; Ehsan, Afshin; Wilson, Sean R.; Goncalves, John; et al.
Abstract : Background: This analysis evaluated echocardiographic predictors of hypoattenuated leaflet thickening (HALT) in low-risk patients undergoing transcatheter aortic valve replacement and assessed 1-year clinical and hemodynamic consequences. HALT by computed tomography may be associated with early valve degeneration and increased neurological events. Methods: Echocardiograms were performed at baseline, discharge, 30 days, and 1 year post-procedure. Four-dimensional contrast-enhanced computed tomography assessed HALT at 30 days. Independent core laboratories analyzed images. Doppler hemodynamic parameters were tested in a univariable regression model to identify HALT predictors. One-year clinical and hemodynamic outcomes were compared between HALT (+) and (−) patients. Results: Analysis included 170 patients with Sapien 3 valves and diagnostic 30-day computed tomographies, of whom 27 (16%) had HALT. Baseline characteristics were similar between groups. After transcatheter aortic valve replacement, aortic flow was nonsignificantly reduced in patients who developed HALT. Regression analysis did not show significant association between baseline or discharge valve hemodynamics and development of HALT at 30 days. Patients with HALT had smaller aortic valve areas (1.4±0.4 versus 1.7±0.5 cm 2 ; P =0.018) and Doppler velocity index (0.4±0.1 versus 0.5±0.1; P =0.003) than those without HALT at 30 days but not at 1 year. There was no difference in aortic mean gradient at 30 days. There was no difference between the groups in New York Heart Association class, 6-minute walk distance, and mortality at 1 year. Conclusions: There were no early hemodynamic predictors of HALT. At 30 days, patients with HALT had worse valve hemodynamics than those without HALT, but hemodynamic and clinical outcomes at 1 year were similar. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT02628899. Abstract : Supplemental Digital Content is available in the text.